MANAGEMENT OF GUIDANCE AND COUNSELING ADMINISTRATION IN STRENGTHENING THE PROFESSIONAL COMPETENCE OF GUIDANCE AND COUNSELING TEACHERS AT GEMBALA BAIK SENIOR HIGH SCHOOL, PONTIANAK - Vitaria Esther Brigitha; Muhammad Asrori; Eni Rosnija; Ida Rochmawati; Marinu Waruwu (SOSIOEDUKASI, 2026)
This study aims to describe the management of guidance and counseling (GC) administration in strengthening the professional competence of guidance and counseling teachers at SMA Gembala Baik Pontianak. The research employed a descriptive qualitative. Data were collected through in-depth interviews, observations, and documentation studies involving guidance and counseling teachers, the principal, vice principals, students, and parents. Data analysis used the interactive model of Miles and Huberman, consisting of data reduction, data display, and conclusion drawing. The findings indicate that the management of guidance and counseling administration has been implemented through planning, organizing, implementation, and evaluation stages; however, it has not yet been optimal in terms of service documentation and the scheduling of face-to-face counseling sessions. The management of GC administration contributes to strengthening the professional competence of guidance and counseling teachers, particularly in mastering service programs, applying professional ethics, and evaluating services. The main constraints include the limited number of guidance and counseling teachers, high administrative workload, and limited service time. Solutions include strengthening school coordination, utilizing administrative technology, and enhancing managerial support.